Desenvolvimento, caracterização e potenciais aplicações de blendas e compósitos baseados em alginato, carboximetilcelulose e xantana - Kláudia Maria Machado Neves Silva (2020)
Natural polymers are being targeted for forming biodegradable plastic films. However, these materials are usually less resistant than conventional polymers, mainly because they can absorb a lot of water from the environment. In order to minimize this problem, it was proposed to prepare polymeric films from the combination of two natural polymers based on alginate or xanthan and carboxymethylcellulose (CMC). For the mixture of the polymers, only the pH change was used (with the neutral medium, pH close to 7, for the mixture of alginate and CMC and the basic medium, pH close to 13, for mixtures of alginate or xanthan and CMC). The results obtained were divided into three sections, the first one focused on samples prepared in a basic medium, and the second and the third focused on films prepared in a neutral medium. Thus, in the first section, the physical and chemical properties of the formed films were evaluated. In the second, a composite with cellulose nanocrystals was prepared. And the third section consisted of make crosslinking, from the combination of calcium and iron ions or the use of epichlorohydrin or the use of a hydrophobic coating on films, in order to control and reduce the rate of swelling and evaluate the release of substances. The results obtained indicated that the films prepared in a basic medium showed a lower rate of transmission and permeation of water vapor and, consequently, from qualitative analysis, they were more effective in protecting against fruit ripening. The film prepared in a neutral medium had the highest rate of vapor transmission and the least rate of swelling. Its nanocomposite had the highest modulus of elasticity, but it did not reduce the rate of swelling of the material. The cross-linking test contributed to the reduction of the swelling rate and to the increase of the degradation time. It is worth noting that the combination of the addition of nanocrystals with crosslinking from metal ions in alginate and CMC films was presented as a potential substitute for epichlorohydrin, a reagent considered toxic. Thus, from this study, it was possible to obtain polymeric films of low production cost, which presented a modulus of elasticity comparable to conventional polymers, and which may be able to act as food packaging or release substances in the environment in which they will be placed.